The Mnn10/Anp1-dependent N-linked outer chain glycan is dispensable for Candida albicans cell wall integrity. Issue 1 (25th March 2022) - Dean, Neta; Jones, Rachel; DaSilva, Justin; Chionchio, Gregory; Ng, Henry
Abstract: Candida albicans cell wall glycoproteins, and in particular their mannose-rich glycans, are important for maintaining cellular integrity as well as host recognition, adhesion, and immunomodulation. The asparagine ( N )-linked mannose outer chain of these glycoproteins is produced by Golgi mannosyltransferases (MTases). The outer chain is composed of a linear backbone of ∼50 α1, 6-linked mannoses, which acts as a scaffold for addition of ∼150 or more mannoses in other linkages. Here, we describe the characterization of C. albicans OCH1, MNN9, VAN1, ANP1, MNN10, and MNN11, which encode the conserved Golgi MTases that sequentially catalyze the α1, 6 mannose outer chain backbone. Candida albicans och1Δ/Δ, mnn9Δ/Δ, and van1Δ/Δ mutants block the earliest steps of backbone synthesis and like their Saccharomyces cerevisiae counterparts, have severe cell wall and growth phenotypes. Unexpectedly, and in stark contrast to S. cerevisiae, loss of Anp1, Mnn10, or Mnn11, which together synthesize most of the backbone, have no obvious deleterious phenotypes. These mutants were unaffected in cell morphology, growth, drug sensitivities, hyphal formation, and macrophage recognition. Analyses of secreted glycosylation reporters demonstrated that anp1Δ/Δ, mnn10Δ/Δ, and mnn11Δ/Δ strains accumulate glycoproteins with severely truncated N -glycan chains. This hypo-mannosylation did not elicit increased chitin deposition in the cell wall, which in other yeast and fungi is a key compensatory response to cell wall integrity breaches. Thus, C. albicans has evolved an alternate mechanism to adapt to cell wall weakness when N -linked mannan levels are reduced.